Nanografted Substrata and Triculture of Human Pericytes, Fibroblasts, and Endothelial Cells for Studying the Effects on Angiogenesis - Kim, Tae Hee; Kim, Soo Hyun; Leong, Kam W.; Jung, Youngmee (MARY ANN LIEBERT, INC, 2016)
For the successful treatment of severe wounds, angiogenesis must be induced to provide a sufficient blood supply to the wound site. There have been many studies on various structural and biochemical factors regulating angiogenesis, such as surface topography, surface modifications, angiogenic factors, and various cell types. However, there is a paucity of research on the effects of micro- and nanoscale topography and the application of pericytes in angiogenesis. In this study, we utilized nanoscale topography combined with a triculture system consisting of human pericytes, fibroblasts, and endothelial cells. We investigated the effects of the nanografted substrata and a triculture system on proangiogenic therapies in vitro. Human dermal fibroblasts and human umbilical vein endothelial cells were seeded with human pericytes from the placenta directly onto nanografted substrata composed of polydimethylsiloxane. We demonstrated that key elements of angiogenesis, including segment and capillary-like tubular structure formation, as well as the secretion of extracellular matrix, were increased by interaction between the nanografted substrata and the coculture containing pericytes. Thus, nanografted surfaces and triculture systems containing human pericytes, fibroblasts, and endothelial cells promote angiogenesis.
Keywords: SMOOTH-MUSCLE-CELLS; POLYMER-DEMIXED NANOTOPOGRAPHY; MULTIPLE GROOVED SUBSTRATA; SCALE TOPOGRAPHY; SURFACE-FEATURES; VESSEL FORMATION; GROWTH-FACTOR; ADHESION; COCULTURE; PROLIFERATION